Zasada podziału władz na szczeblu stanowym w USA: Tom II - Stolicki, Dariusz (Księgarnia Akademicka Publishing, 2025)
THE PRINCIPLE OF SEPARATION OF POWERS AT THE STATE LEVEL IN THE USA Separation of powers is one of the cornerstone principles of American constitutional law. However, while the implementation of this principle at the federal level has been extensively studied, there is a relative paucity of comparative research on separation of powers at the state level. The present book seeks to fill that gap by comprehensively analyzing how separation of powers operates at the state level. The book focuses on three principal research questions: First: What are the key differences between state and federal versions of the separation of powers? Second: Where do significant interstate variations appear? Third: Do similarities between the states reflect shared political traditions, nationwide historical influences or interstate constitutional dialogue? The book consists of six chapters.